Study of WH production through vector boson scattering and extraction of the relative sign of the W and Z couplings to the Higgs boson in proton-proton collisions at s=13TeV - A. Hayrapetyan; A. Tumasyan; W. Adam; J.W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P.S. Hussain; M. Jeitler; N. Krammer; A. Li; et al. (Physics Letters B)
A search for the production of a W boson and a Higgs boson through vector boson scattering (VBS) is presented, using CMS data from proton-proton collisions at s=13TeV collected from 2016 to 2018. The integrated luminosity of the data sample is 138fb−1. Selected events must be consistent with the presence of two jets originating from VBS, the leptonic decay of the W boson to an electron or muon, possibly also through an intermediate τ lepton, and a Higgs boson decaying into a pair of b quarks, reconstructed as either a single merged jet or two resolved jets. A measurement of the process as predicted by the standard model (SM) is performed alongside a study of beyond-the-SM (BSM) scenarios. The SM analysis sets an observed (expected) 95% confidence level upper limit of 14.3 (9.9) on the ratio of the measured VBS WH cross section to that expected by the SM. The BSM analysis, conducted within the so-called κ framework, excludes all scenarios with λWZ<0 that are consistent with current measurements, where λWZ=κW/κZ and κW and κZ are the HWW and HZZ coupling modifiers, respectively. The significance of the exclusion is beyond 5 standard deviations, and it is consistent with the SM expectation of λWZ=1.